Applying the Dimensional Model of Adversity and Psychopathology to the study of ACEs in children and adolescent in residential care - Gaitán, Sabina D.; García-Durán, Laura; Romero Códez, Sonia; Fernández-Baena, Francisco Javier; Salas-Martínez, María Dolores (My University, 2025)
Adverse Childhood Experiences (ACEs) is one of the most significant environmental factors influencing the development of cognitive, social and mental health problems throughout life. The Dimensional Model of Adversity and Psychopathology (DMAP) aims to specify the mechanisms by which early adversity affects development. This model differentiates between two dimensions of adversity: threat, characterised by exposure to atypical situations that pose a perceived risk (such as physical abuse); and deprivation, which is the absence of expected experiences that facilitate a healthy child's development (such as neglect). This study describes the application of the DMAP in a project developed by the University of Malaga with young people in residential care. Children and adolescents aged between 9 and 16 years old living in 22 residential homes in Malaga province were assessed. An extensive evaluation of the files of each young person was carried out and, based on the indicators included in the classification system of maltreatment of the Government of Andalusia (SIMIA), an exhaustive codification was made. Each type of adversity, the developmental stage and the chronicity of the exposure was recorded. Among the most relevant and descriptive results, it was found that over 70% of the young people had suffered more than one ACE before entering the protection system and that 98% of them had suffered neglect in their first reported adversity. In addition, it was also found that those children and adolescents who had suffered early ACEs (before age 3) showed greater problems in emotional regulation. The results also show that longer time in the residential home is related to less internalizing and attentional problems. Finally, the theoretical and methodological contributions of this model to understanding the effects of ACEs on human development will be discussed.
Keywords: Cuidadores - Congresos; Niños - Protección, asistencia, etc. - Congresos; Residential Care; Adverse Childhood Experiences; Adolescence